Internetworking connectionless and connection oriented networks. - Veeraraghavan, M.
The use of connection-oriented (CO) networks for the transport of IP traffic is seen to have value to both users and service providers. Given the expectation that most endpoint-generated traffic will be in the form of connectionless (CL) IP datagrams, we address the problem of how to internetwork a CL (IP) network with a CO network. CO networks can be packet-switched or circuit-switched. Examples of packet-switched CO networks include ATM and MPLS networks, in which resource reservations are made at the ATM or shim layer, and IP-switch-based networks, in which resource reservations are made at the IP layer. Examples of circuit-switched networks include SONET/SDH and WDM networks that consist of programmable optical crossconnects. We consider the internetworking problem for two modes of operation of CO networks: provisioned, in which connections are set up a priori, and switched, in which connections are set up on demand. The main focus of this article is on the more complex problem: the internetworking of CL IP networks with CO networks operated in a switched mode. Our solution consists of (i) interworking user plane protocols with protocol conversion in some cases instead of always using protocol encapsulation, (ii) interworking routing protocols by either simply having gateways know routing information of both networks or having all nodes know routing information of both networks, and (iii) interworking signaling protocols by using application- or transport-layer end-to-end handshakes to trigger connection setups through the CO network. We demonstrate throughput improvements with our integrated routing interworking scheme over the MPOA IP-ATM internetworking solution for two example networks
Keywords: ATM; CL IP networks; IP datagrams; IP layer; IP traffic; IP-switch-based networks; MPLS; MPOA IP-ATM internetworking solution; SONET/SDH.; WDM; Circuit-switched networks; Connection oriented networks; Connection setups; Connectionless oriented networks; End-to-end handshakes; Endpoint-generated traffic; Internetworking; Packet-switching.; Programmable optical crossconnects; Protocol conversion; Protocol encapsulation; Resource reservations; Routing protocols; Shim layer; Signaling protocols; User plane protocols